O drama da multidão e os trágicos black blocs: a busca do constituinte como destino e a ação direta. - Passetti, Edson; Augusto, Acácio (Ecopolítica, 2014)
Disponível em: http://www.pucsp.br/ecopolitica/galeria/galeria_ed9.html